Finnish Direct Investments in the Baltic Market, Mobile Phone Service Centers - Kanervo (os. Kaustinen), Hanna (My University, 2008)
The amount of Finnish foreign direct investments has grown over the years as companies have moved from export to having a subsidiary abroad. The Baltic countries have become a gateway to the east for Finnish companies by offering reasonable priced labor and strong buying power with a large market. The main focus of this thesis is to find out the choice of ownership structure and form of investment for Finnish mobile phone service centers investing in the Baltic market. The theoretical framework of this thesis has been built from previous studies. Strategic motives behind the different production types are studied based on Dunning’s (1992, 1993) OLI-theory. The most important features of different ownership arrangements and form of investments, as well as factors that will affect the choice of ownership and form of investment, are studied based on Larimo’s (1999a, 1999b) studies. The table of strategic motives and assumptions for ownership and form of investment are then build based on a theoretical framework and is tested in the empirical part of this thesis. The empirical part is conducted by qualitative case studies on two Finnish mobile phone service centers investing in the Baltic market. The data for the case studies is gathered by semistructured interviews via e-mail, telephone and face-to-face. The findings of this study indicate that market seekers investing in the Baltic States who are targeting to gain more market share, increased revenues and to take advantage of low labor and operational costs, but would like to keep all control to them, will enter the Baltic market with wholly owned green field investments. The findings of this study will also suggest that market and efficiency seeking investors interested in already established customers and supplier contacts, to take advantage of low labor costs, but still keep most of control on them, will enter the Baltic market with joint acquisition. The conclusions and further investment suggestions according to this study must be exercised with caution and only be drawn on the basic association, since the examination of the motives for ownership and form of investment would require more longitudinal research to find actual correlations between motives and ownership type and form.
Keywords: Foreign Direct Investment; Green Field Investment; Acquisition; Joint Venture; Mobile after Sales Market; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|